2019
DOI: 10.1007/s11920-019-1085-1
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Maternal Stress and the Cascade of Risk to Schizophrenia Spectrum Disorders in Offspring

Abstract: Purpose of Review-Disruptions in fetal development (via genetic and environmental pathways) have been consistently associated with risk for schizophrenia in a variety of studies. Although multiple obstetric complications (OCs) have been linked to schizophrenia, this review will discuss emerging evidence supporting the role of prenatal maternal stress (PNMS) in the etiology of schizophrenia spectrum disorders (SSD). In addition, findings linking PNMS to intermediate phenotypes of the disorder, such as OCs and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 143 publications
0
32
0
1
Order By: Relevance
“…5 Center for Mind, Brain and Behavior (CMBB), Hans-Meerwein-Strasse 6, Marburg 35043, Hessen, Germany. 6 Collaborative Research Center 936 (SFB936) -Project C6 -Third Funding Period, Justus-Liebig University, Klinikstrasse 36, Giessen 35392, Hessen, Germany.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Center for Mind, Brain and Behavior (CMBB), Hans-Meerwein-Strasse 6, Marburg 35043, Hessen, Germany. 6 Collaborative Research Center 936 (SFB936) -Project C6 -Third Funding Period, Justus-Liebig University, Klinikstrasse 36, Giessen 35392, Hessen, Germany.…”
Section: Fundingmentioning
confidence: 99%
“…The model implies that genetic makeup predisposes the subject to be easily affected by stress, which would show inflammatory responses later in life [5]. A review by Lipner et al has concluded that prenatal maternal stress (e.g., prenatal infection/inflammation, decreased fetal growth, hypoxia-related obstetric complications) has been linked to the development of schizophrenia in offspring [6].…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal stress refers to the stress suffered by mothers during the gestational period that affects the offspring [31]. In humans, it has been demonstrated that prenatal exposure to unpredictable or chronic stressors, such as adverse life events, natural disasters or social pressures [34,35], increases the risk of suffering several psychopathologies, including schizophrenia [36][37][38], ASD [39,40], and major depression-and anxiety-related disorders [41]. Importantly, recent studies have confirmed what has long been theorized, but not yet observed in humans: that stress suffered during pregnancy is reflected in the connectional characteristics of the offspring's brain, independent of the influences of the postnatal environment [42].…”
Section: Stress Exposure During the Prenatal Period: Prenatal Stressmentioning
confidence: 99%
“…Studying the single contributions of specific environmental exposures in the pathogenesis of schizophrenia is challenging, as these factors are dynamically interconnected and interdependent over time. Prenatal maternal stress, for example, may increase the risk for schizophrenia in offspring through maternal subjective distress, obstetrical complications, health-impairing behaviors, or other pathways (King et al, 2010;Lipner et al, 2019). These pathways converge downstream to biological mechanisms such as maternal immune activation (Lipner et al, 2019).…”
Section: Letter To the Editormentioning
confidence: 99%
“…Prenatal maternal stress, for example, may increase the risk for schizophrenia in offspring through maternal subjective distress, obstetrical complications, health-impairing behaviors, or other pathways (King et al, 2010;Lipner et al, 2019). These pathways converge downstream to biological mechanisms such as maternal immune activation (Lipner et al, 2019). Further, prenatal maternal stress, such as daily life hassles, may also be a proxy variable for inheritable or familial vulnerability factors (King et al, 2010).…”
Section: Letter To the Editormentioning
confidence: 99%